The Physiology, Pharmacology and Therapeutic Manipulation of the Internal Anal Sphincter - Oliver M Jones; Alison F Brading; Neil J McC Mortensen (Canadian Journal of Gastroenterology)
Recent research into the physiology and pharmacology of the internal anal sphincter has elucidated the importance of this structure in health and disease. Its pharmacological manipulation for therapeutic gain has focused mainly on agents to reduce internal anal sphincter tone, a ‘chemical sphincterotomy’ that might heal chronic anal fissure. However, drugs to increase sphincter tone, and augment intermittent and appropriate relaxation are also being evaluated. The initial results with this medical approach to anorectal disease have often been disappointing, failing to match the results achievable with surgery, and many of these drugs have a high rate of side effects in the short term. However, clinical trials have yet to establish the optimum doses, dose intervals and routes of administration for many of these therapies. Furthermore, it is uncertain whether this medical approach should be applied to all patients or just to an as yet undefined subgroup. Certainly, even in the current environment of uncertainty, there is little reason not to try medical manipulation of the internal sphincter as first-line treatment. Surgery remains an option for treatment failures; patients responding to pharmacological manipulation of the internal anal sphincter are spared the long term risks of continence that are inherent in many surgical procedures on the anorectum.